2021
DOI: 10.1021/acsaem.1c00220
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Surface Properties for Electrodeposited Cu(In,Ga)Se2 Films by (NH4)2S Solution at Room Temperature

Abstract: Fabricating chalcopyrite Cu­(In,Ga)­Se2 (CIGS) films from electrodeposition is one of the most effective ways to lower the production cost and energy consumption compared with that from vacuum methods. However, this process often produces a pronounced rough surface with impurity phases, induces the accumulation of gallium, and results in a low surface band gap. In this work, ammonium sulfide ((NH4)2S, AS) solution treatment is used as a single way to realize the optimization of the distribution of elements on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 38 publications
2
5
0
Order By: Relevance
“…It is observed also that, the order of light response intensities is BFTOC > BFTOB > BFTOI, which can be ascribed to the sub-band gap absorption of powder materials. As we know, the significant sub-band gap absorption of films is indicative of the presence of the secondary phases or the band tailing [44][45][46][47]. This observation suggests the BFTOC powder has the lowest defect concentrations and photogenerated carrier recombination compared with the two other samples, which should be the reason for the highest performance of CO2 reduction for BFTOC sample, as is consistent with the SEM results.…”
Section: Photocatalytic Co 2 Reduction Performance For Bftox Materialssupporting
confidence: 84%
“…It is observed also that, the order of light response intensities is BFTOC > BFTOB > BFTOI, which can be ascribed to the sub-band gap absorption of powder materials. As we know, the significant sub-band gap absorption of films is indicative of the presence of the secondary phases or the band tailing [44][45][46][47]. This observation suggests the BFTOC powder has the lowest defect concentrations and photogenerated carrier recombination compared with the two other samples, which should be the reason for the highest performance of CO2 reduction for BFTOC sample, as is consistent with the SEM results.…”
Section: Photocatalytic Co 2 Reduction Performance For Bftox Materialssupporting
confidence: 84%
“…According to the report from Buffière et al., the AS solution treatment was performed on the CIGSe absorber, and the increasing of the Cu 2p peak intensity is related to the slow etching rate of the Cu‐related phase by the AS treatment. [ 17,21 ] Furthermore, for the Zn 2p3/2 peak, a significant banding energy decrease of 0.15 eV is obtained after the AS treatment, and the Sn 3d5/2 peak shifted 0.2 eV toward low binding energy, from 486.5 eV for sample Kes and Kes‐Al 2 O 3 to 486.3 eV for sample Kes‐Al 2 O 3 ‐AS. According to Grenet et al., the peaks of Zn 2p3/2 and Sn 3d5/2 moving toward lower binding energy after AS treatment is considered to be due to the oxidation/deoxidation of the ZnSe and SnSe x phases on the surface, respectively.…”
Section: Resultsmentioning
confidence: 98%
“…It is reported that ammonium sulfide ((NH 4 ) 2 S, referred to as AS) solution treatment on the absorber layer can improve the film's surface properties. [16][17][18][19][20][21][22][23] For example, Buffière et al selectively removed the secondary phase on the surface and modified the surface chemical state by dipping CIGS absorber into AS solution, and the minority carrier lifetime increased about 6-11 ns with different treatment times. [17] The same treatment has been employed for CZTSSe, too.…”
Section: Introductionmentioning
confidence: 99%
“…The relevance of the development of low temperature synthetic procedures of Sb 2 Se 3 is supported by its versatility in terms of device processing, making this material an ideal candidate for temperature-sensitive applications such as tandem solar cells and flexible or transparent substrates. The different etching solutions investigated in this work have been inspired by processes already evaluated and proven effective in other thin film technologies, in particular, HNO 3 -H 3 PO 4 (NP) and Br 2 -methanol (BrM) in CdTe; , KCN, (NH 4 ) 2 S (NHS), and BrM in CIGS; , and KCN, NHS, BrM, KMnO 4 -H 2 SO 4 (KMO), and CS 2 in kesterite, , as presented in Table . For all of these chemical solutions, the initial etching conditions were selected from the optimal ones reported in the literature, and a complementary study was performed by varying the etchant concentration and etching times.…”
Section: Resultsmentioning
confidence: 99%
“…Reduces the surface roughness (better covered by CdS) but also incorporates sulfur (increased bandgap) and removes the impurity phases (reduction of the acceptor Cu-Ga). 32,33 It reduces series resistance, and consequently increases V oc , FF, and efficiency. defects.…”
Section: Br 2 -Meohmentioning
confidence: 99%